Modeling the Interrelationships of Critical Thinking Skills-Dispositions in Questioning Skills of Preservice Language Teachers - Rahmawati, Sophia; Munawarah, Munawarah; @ Khalid, Kartini Aboo Talib; Octavia Kusuma Wardani, Diah; Rachmad Pratama, Deri (Universitas Jambi, Magister Program of English Education Department, 2026)
Questioning skills, in most teacher education discourse, is treated as though it were a matter of technique as if asking better questions were simply a skill to be drilled. This study takes a different position. Drawing on Facione's critical thinking framework, we examine how dispositional and cognitive dimensions of critical thought shape the questioning practices of 111 preservice language teachers during microteaching. Using PLS-SEM, findings confirm that critical thinking disposition predicts both critical thinking skills (t = 5.203, p < .001) and questioning skills directly (t = 4.206, p < .001), while critical thinking skills independently predict questioning quality (t = 3.952, p < .001). CTD and CTS together explain 32% of variance in questioning skills. The remaining variance being, frankly, an invitation for researchers who assume questioning is reducible to pedagogy alone. What emerges from this data is uncomfortable but necessary is being preservice teacher cannot train someone to ask intellectually serious questions if they are not, at some level, an intellectually serious person. Teacher education programs would do well to sit with that.